Pelatihan Senam Pelajar Indonesia Bagi Guru Pendidikan Jasmani Koordinator Wilayah Kesesi - Gilang; Tresnowati, Idah; Widya Putri, Mega (Jurnal Muhammadiyah untuk Olahraga Indonesia, 2021)
Lack of teacher competence in mastering rhythmic gymnastics material to optimize learning through the use of media, the potential possessed by teachers and students, and a willingness to improve skills in rhythmic activity material. The lack of gymnastics learning models which are generally rigid and monotonous causes student interest to decline. This activity aims to provide skills and knowledge to Sports and Health Physical Education teachers regarding Indonesian Student Gymnastics which can be used as a medium in learning rhythmic activities. The approach method in this activity uses demonstration, lecture and discussion methods. The implementation of the activity consists of 5 stages which end with the evaluation of the training results. The result of the training which was attended by 32 participants was an increase in pedagogical competence in understanding and practicing Indonesian Student Gymnastics in learning rhythmic activities, increasing the consistency and responsibility of teachers in delivering rhythmic activity material, which in turn can increase student motivation through Indonesian Student Gymnastics as a learning medium. interesting and in accordance with the needs of movement and the characteristics of elementary school students